Hegel and Character: the place of mindedness between nature and spirit (Revista Eletrônica Estudos Hegelianos, 2024)
This paper is devoted to a systematic analysis of the notion of “character” within Hegel’s thought. So far, this notion has been considered marginal within Hegelian philosophy and has hardly been addressed in the critical literature. This article, however, attempts to argue in favor of the thesis that character plays a prominent role in Hegel’s thought. In this paper we therefore aim to provide (i) a systematic reconstruction of the concept of “character” in Hegel’s Lectures on the Philosophy of History and Lectures on the philosophy of Subjective Spirit in order to show that (ii) the notion of character in Hegel has a greater relevance than hitherto acknowledged, a relevance which invests central notions of his philosophy. Our thesis, more specifically, is that the notion of character turns out to be closely related to load-bearing notions in Hegel’s thought – namely, the notion of self-consciousness (as distinctive element of human rationality) and the notion of the spirit of a people (as a set of sociocultural and dispositional factors that allow different levels of understanding of the autonomy of human rationality). Precisely on the basis of this relevance and the critical issues it brings, such an operation provides the basis for arguing that iii) the Hegelian concept of character has important repercussions both on the contemporary debate on Hegel and on contemporary hegelianisms.